1998
DOI: 10.1001/archsurg.133.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Pancreatoscopy With the Ultrathin Pancreatoscope for Mucin-Producing Tumors of the Pancreas

Abstract: To evaluate the diagnostic accuracy of intraoperative pancreatoscopy with the ultrathin pancreatoscope for the main pancreatic lesions of mucinproducing tumors of the pancreas (MPT). Design: Prospective diagnostic test study with a criterion standard of pathologic examination and masked comparison. Setting: A university hospital. Patients: Twenty-four consecutive patients with MPT referred for surgery in whom endoscopic retrograde pancreatography, endoscopic ultrasonography, and computed tomography had been pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 20 publications
0
61
0
1
Order By: Relevance
“…These authors also found that colloid carcinoma was a favorable prognostic factor independent of patient age, tumor diameter or disease stage. Lastly, debate around the concepts of a local field defect versus disease multicentricity further clouds our understanding of the exact biology of these lesions [13,14,[21][22][23][24][25][26] .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These authors also found that colloid carcinoma was a favorable prognostic factor independent of patient age, tumor diameter or disease stage. Lastly, debate around the concepts of a local field defect versus disease multicentricity further clouds our understanding of the exact biology of these lesions [13,14,[21][22][23][24][25][26] .…”
mentioning
confidence: 99%
“…In addition, all have relatively short mean follow-up periods (maximum 40 mo) further complicating the interpretation of a neoplasm with a known indolent course. Following operation, the risk of recurrence in either the remnant pancreas or distant sites is high (up to 65%) in patients with invasive IPMN [13,14,[21][22][23] . This rate is substantially lower (< 8%) in patients with noninvasive IPMN (adenoma, dysplasia, carcinoma in situ) [13,14,[21][22][23] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because IPMN is characterised by multifocality, total pancreatectomy has been advocated [11] [31] [32]. Advocates of this policy argue on the basis that up to 30% of patients will have multifocality at the time of diagnosis [11] [33] [34]. Furthermore, achieving clear margins does not necessarily mean there would be no missed foci in the pancreatic tissue left behind in the context of a multifocal disease.…”
Section: Managementmentioning
confidence: 99%
“…Thus, this study concluded that peroral pancreatoscopy and pancreatoscopic cytology are indeed useful for locating and diagnosing carcinoma in situ of the pancreas. In 1998, further evidence of the additive value of pancreatoscopy to supplement traditional diagnostic techniques was published [51] . In this report, pancreatoscopy was performed in 24 patients with intraductal mucinous neoplasms of the pancreas.…”
Section: Diagnostic Applicationsmentioning
confidence: 99%